Randomized phase II study of docetaxel versus paclitaxel in patients with esophageal squamous cell carcinoma refractory to fluoropyrimidine- and platinum-based chemotherapy: OGSG1201. (September 2021) - Yamamoto, Sachiko; Kawakami, Hisato; Kii, Takayuki; Hara, Hiroki; Kawabata, Ryohei; Kawada, Junji; Takeno, Atsushi; Matsuyama, Jin; Ueda, Shugo; Okita, Yoshihiro; Endo, Shunji; Kimura, Yutaka; et al.
Abstract: Background: There is no standard chemotherapy for esophageal squamous cell carcinoma (ESCC) refractory to first-line fluoropyrimidine- and platinum-based chemotherapy. We therefore performed a randomized, selection-design phase II trial to compare docetaxel (DTX) and paclitaxel (PTX) in this setting. Patients and methods: Eligible patients were randomly assigned to receive either DTX (70 mg/m 2 on day 1 of each 21-day cycle) or PTX (100 mg/m 2 on days 1, 8, 15, 22, 29 and 36 of each 49-day cycle). The primary end-point was overall survival (OS), and secondary end-points included progression-free survival (PFS), time to treatment failure (TTF), response rate (RR) and safety. Results: Seventy-eight eligible patients ( N = 39 in each group) were included for efficacy analysis. OS was significantly longer in the PTX group than in the DTX group (median, 8.8 versus 7.3 months; hazard ratio [HR], 0.62; P = 0.047). A significant benefit of PTX over DTX was also apparent in PFS (median, 4.4 versus 2.1 months; HR, 0.49; P = 0.002) and TTF (median, 3.8 versus 2.1 months; HR, 0.45; P < 0.001). RR (25.6% versus 7.7%, P = 0.065) were higher in the PTX group than in the DTX group. Compared to the PTX group, neutropenia (28% versus 80%) and leukopenia (28% versus 76%) of grade ≥3 as well as febrile neutropenia (0% vs. 46%, P < 0.0001) occurred more frequently in the DTX group. Conclusion: PTX showed a significantly better efficacy as well as a more manageable toxicity compared with DTX. Clinical trial registration: UMIN000007940. Highlights: This study is the first to compare PTX to DTX in ESCC in second-line setting. PTX showed significantly better efficacy as well as less toxicity than DTX. Our data suggested the validity of PTX as second-line therapy was not reliant on ICI.